Clinical analysis of foreign-born patients with tuberculosis found in Malaysia - Nissapatorn, V.; Kuppusamy, I.; Wan-Yusoff, W.S.; Anuar, A.K. (2005)
. In this retrospective study, we investigated 263 foreign patients who were diagnosed as having tuberculosis at the National Tuberculosis Center (NTBC) from January 2001 to December 2002. The age range was 14-72 years, with a mean of 33.3 Â± 9.95 years. The study subjects were predominantly males (60) and females comprised 40, where the greater impact of tuberculosis was observed in the young and active ones (up to 34 years of age), than middle-age (up to 54). A significantly higher percentage of these patients were from the Southeast Asian countries (87) and particularly occurred in single male (47.5) and married female (71.4) patients (p<0.05). We also found that tuberculosis was significantly higher in female (50.5) and male (64) with smoking laborers (p<0.05). Fever (70), cough (90.5) and BCG vaccination status showed a significantly higher percentage in male patients (p<0.05), whereas lymphadenopathy (22) was found in a significantly higher percentage in females (p<0.05). Overall, pulmonary disease (94.3) occurred more commonly in males and the pleura (3.2) was the most common site of disseminated tuberculosis. By contrast, the lymph node (11.4) and miliary (4.8) forms were the more common extrapulmonary tuberculosis in females. More males had higher percentage of treatment completed at â¥ 6 (38) and â¥ 9 (13.3) months in pulmonary tuberculosis, whilst, more females showed higher percentage of treatment completed (8.7) in extrapulmonary tuberculosis. Surprisingly, more women showed noncompliance to the anti-tubercular therapy than their counterpart in this study